IMPLEMENTATION OF THE INTEGRITY RIGHTS OF UNDERAGE CHILDREN BASED ON THE DETERMINATION OF THE STATE COURT CASE STUDY AT THE NOTARY OFFICE OF FAJRI ALBASTRA, S.H., M.KN - Zahratul Aini; Rahmi Ayunda (Universitas Internasional Batam, 2022)
This study was conducted to analyze the determination of the Batam District Court Number 245/Pdt.P/2021/PN.BTM regarding the guardianship of minors in buying and selling houses carried out by the heirs. The problem used in writing this article is about the implementation and accountability of guardianship in buying and selling houses due to inheritance, the judge's basic considerations in determining the guardianship of minors in the process of buying and selling houses because it is to finance the life and education of the applicant's child. The research method used by the author in this study is an empirical juridical approach, this juridical approach is carried out to examine various laws and regulations related to the determination of child guardianship on the responsibility of parents in buying and selling houses due to inheritance. An empirical approach is carried out to see the implementation of parents representing minors for legal actions inside and outside the court